Innovative Staffing Solutions to Nursing Shortages in Acute Mental Health Inpatient Wards. (17th February 2022) - Ma, Eva; Kritsimali, Afroditi; Olby-Clements, Ben; Boyd, Kyle; Demirbasa, Belinda
Abstract: The aim of this pilot project was to investigate the perceived impact of a newly introduced therapeutic staffing model at Kent and Medway NHS and Social Care Partnership Trust (KMPT). Questionnaires were distributed to patients and staff across four wards and analysed for the purposes of getting a better understanding from patients and staff on how the model was working. Results indicate that the therapeutic staffing model was well received by patients, although staff perception was more mixed. Amongst patients, themes in staffing, therapeutic input and ward environment were identified. Amongst staff themes: shift patterns, ward duties/workload, and morale were identified. The new model appears promising, although there are some issues identified. Recommendations were made in terms of improving team cohesiveness, sense of value and professional identities.